(untitled) (Contemporary Mathematics, 2020)
Boundary value problems for linear stationary dispersive equations of order 2l + 1, l ∈ N with general linear boundary conditions have been considered on finite intervals (0, L). The existence and uniqueness of regular solutions have been established.